The effect of rehabilitation exercises with diversity of resistors and moving balance tools in rehabilitating rupture of the second type of muscles for the thigh of the soccer players - Al -Zubaidi , Firas (Journal of Physical Education, 2025)
The aim of the research is to prepare rehabilitation with the diversity of resistors and moving balance tools for football players with rupture of the second type of muscles of the thigh, identifying the effect of qualifying exercises with the diversity of resistors and moving balance tools in developing the angle of dimensions out and the strength of the connective muscles of the interior and the level of pain for football players with a rupture of the second type of muscles of the thigh, Experimental design, the experimental and control groups, and the boundaries of the research community with football players who are injured by the Physiotherapy Division of the Baghdad Education Hospital in the Department of Medicine City, whose total number (17) were injured, and they are in nature from various popular clubs in Baghdad and they are ages between (17-19) years, of whom he was chosen for the research sample (16) injured (94.118 %) of their society. Then they divided into two equal number groups, and one of them was chosen as a livestock to be the experimental group, and the other is controlled, and the tests of the identical to recover from this injury were identified, and the preparation of (18) treatment sessions were applied by (3) sessions per week, and for a period of (6) weeks on the injured of the experimental group, and treatment of tribal and remote tests after the experiment ends with a system (SPSS) for the conclusions that the qualifying exercises with the diversity of resistors and moving balance tools are suitable for therapeutic sessions of the injured football players., And it has a positive effect in developing a force that includes the interior of the connective muscles of the thigh, and it has a positive impact on developing the dimensions of the dimensions outside of the connective muscles of the thigh, and it has a positive effect in reducing the level of pain degree V The connective of the thigh is for football players with a rupture of the second type, The recommendations were that it was necessary not to exaggerate the diversification between resistors and moving balance tools in therapeutic sessions of the luxury muscles of the thigh of the soccer players with rupture of the second type, and the level of pain degree V.A.S) must be adopted) and with caveats when the difficulties of the qualifying exercises for the rehabilitation of the connective muscles of the thigh for the soccer players with the rupture of the second type to preserve Muscle fiber from increased rupture in this affected muscle